Synaptic Protein Phosphorylation Networks Are Associated With Electroacupuncture-Induced Circadian Control in the Suprachiasmatic Nucleus - Lu, Xiaoxiao; Zhou, Minjie; Liu, Nannan; Zhang, Chengshun; Zhao, Zhengyu; Cai, Dingjun (Frontiers in Genetics, 2021)
Phosphorylation is one of the most important post-translational modifications and regulates the physiological process. While recent studies highlight a major role of phosphorylation in the regulation of sleep-wake cycles to a lesser extent, the phosphoproteome in suprachiasmatic nucleus (SCN) is not well-understood. Herein, we reported that the EA treatment elicits partial reparation of circadian rhythmicity when mice were prolonged exposed to constant darkness. We investigated the effects of EA on circadian rhythms in constant darkness between EA stimulation and free-running control. Next, mass spectrometry-based phosphoproteome was utilized to explore the molecular characteristics of EA-induced phosphorylation modification in the SCN. A total of 6,192 distinct phosphosites on 2,488 proteins were quantified. Functional annotation analysis and protein-protein interaction networks demonstrated the most significant enriched phosphor-proteins and phosphosites involved in postsynapse and glutamatergic synapse. The current data indicated that most of the altered molecules are structural proteins. The target proteins, NMDAR and CAMK2, were selected for verification, consistent with the results of LC-MS/MS. These findings revealed a complete profile of phosphorylation modification in response to EA.